PERAN BRAND IMAGE DALAM MEMEDIASI PENGARUH E-WOM TERHADAP NIAT MENGGUNAKAN GOJEK DI KOTA DENPASAR - Putra, I Ketut Pande Mahesa; Rastini, Ni Made (E-Jurnal Manajemen, 2022)
The development of internet technology in the current era of globalization has a major impact on people's daily lives, one of which is in the field of business or online commerce. Along with technological developments, transportation companies have also had a positive impact in terms of marketing and sales of services that are now utilizing internet technology. Gojek is a technology-based transportation service provider company from Indonesia. In an effort to increase consumer intention to use Gojek, the company creates a new breakthrough to create positive E-WOM so as to increase Gojek's brand image. This study aims to determine the role of Brand Image in mediating E-WOM towards the intention to use Gojek. This research was conducted in Denpasar City by using Gojek as the research object. This study involved 108 respondents with a non-probability sampling technique with a purposive sampling method. Data collection was carried out using a questionnaire distributed via Google Forms. The data analysis techniques used in this study were path analysis, classical assumption test and sobel test. The results of this study indicate that Brand Image positively and significantly mediates the effect of E-WOM on the intention to use Gojek in Denpasar City. This research is expected to be an input as a consideration for Gojek in increasing innovation and service quality according to community needs. Keywords: Brand Image, E-WOM, Purchase Intention